VD_FINDINFO Faillite / 2020 / 34 vom 23. Dezember 2020 - VD Tribunal cantonal (2020)
FAILLITE SANS POURSUITE PRÉALABLE, REJET DE LA DEMANDE, OBLIGATION D'ANNONCEREN GÉNÉRAL, SURENDETTEMENT | 725 CO, 725a al. 1 CO, 728c al. 3 CO, 192 LP, 194 al. 1 LP